Implementation of Restorative Justice in the Criminal Act of Underage Girls Running Away - Ganda, Aria; Raharjo, Trisno (Faculty of Law, Universitas Pekalongan, 2024)
This research explores the implementation of restorative justice in handling runaway cases of minors. As a legal paradigm, restorative justice offers a holistic approach that involves restoring relationships disrupted by criminal acts. The focus is not only on punishment but rehabilitation, reconciliation, and restoration for victims and perpetrators. In the context of cases of runaway minors, this approach is a relevant and sustainable alternative. This research highlights variations in implementing restorative justice, indicating the need for more precise guidelines and standards to ensure consistency and effectiveness. Differences in local context and culture also play an essential role in successful implementation. Challenges in stakeholder participation highlight the need for further efforts to build trust and support the involvement of all relevant parties. In addition, this research underscores the need for ongoing support for runaway children following the restorative justice process, strengthening the argument for the integration of long-term recovery programs.